2010
DOI: 10.1158/1055-9965.epi-10-0703
|View full text |Cite|
|
Sign up to set email alerts
|

Volumetric Breast Density from Full-Field Digital Mammograms and Its Association with Breast Cancer Risk Factors: A Comparison with a Threshold Method

Abstract: Introduction: Breast density, a strong breast cancer risk factor, is usually measured on the projected breast area from film screen mammograms. This is far from ideal, as breast thickness and technical characteristics are not taken into account. We investigated whether volumetric density measurements on full-field digital mammography (FFDM) are more strongly related to breast cancer risk factors than measurements with a computer-assisted threshold method.Methods: Breast density was measured on FFDMs from 370 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
46
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 27 publications
13
46
1
Order By: Relevance
“…Our findings about the correlation with Cumulus agree with those from earlier reports on volumetric methods (29,30,(32)(33)(34)39), showing a strong correlation for total breast volume and percent dense volume, but a weak correlation for the absolute dense volume. This difference in correlation for the absolute dense tissue is not unexpected as volumetric and area-based methods measure different aspects of mammographic density.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings about the correlation with Cumulus agree with those from earlier reports on volumetric methods (29,30,(32)(33)(34)39), showing a strong correlation for total breast volume and percent dense volume, but a weak correlation for the absolute dense volume. This difference in correlation for the absolute dense tissue is not unexpected as volumetric and area-based methods measure different aspects of mammographic density.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, both percent and absolute dense volumes were associated with all known density determinants in the expected direction (Table 3 and Supplementary Table S4). The contrasting effect of BMI on percent and absolute dense volume has been described previously (29,(32)(33)(34) and underscores the notion that the inverse association with percent density is mainly due to the positive correlation between BMI and the amount of nondense fatty tissue. Mammographic density is not only influenced by reproductive and hormonal factors, but is also genetically determined.…”
Section: Discussionsupporting
confidence: 70%
“…36 It should be noted though that these numbers are volumetric measures of the breast density, which have a much smaller range than area-based measures such as the BIRADS classification of mammographic breast density. 37 We have also performed cone beam CT scans on the same postmortem breast samples to determine the breast density from the reconstructed 3D CT images. The range of breast densities measured by a standard FCM algorithm on the CT measurements is from 4% to 52%, 32 which matches well with the result from the bias-field-corrected MRI images.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] The data for volumetric measures are still being collected; previous studies have reported that early implementations were very sensitive to errors in the reported physics factors [10][11][12] and the risk results are disappointing, 13 but more recent implementations have found more promising results. [14][15][16] The basic assumption behind volumetric techniques is that the breast consists of fat and fibroglandular tissue and that we can use X-ray physics parameters for each image to estimate X-ray attenuation between each pixel and the X-ray source, hence, the various contributions of those tissue types between that pixel and the X-ray source. Where volumetric technique differs is in the implementation used to get to the volumetric measures.…”
Section: Introductionmentioning
confidence: 99%